A MOBILE-DEVICE-SUPPORTED PEER-ASSISTED LEARNING SYSTEM FOR COLLABORATIVE EARLY EFL READING - Yu-Ju Lan; Kuo-En Chang; Yao-ting Sung (Language Learning and Technology)
Collaborative learning methods which emphasize peer interaction have been widely applied to increase the intensity and effectiveness of EFL reading programs. However, simply grouping students heterogeneously and assigning them group goals does not guarantee that effective collaborative learning will ensue. The present research includes two studies. In Study One, the weaknesses of collaborative learning in a traditional EFL setting were observed. Then, in Study Two, a mobile-device-supported peer-assisted learning (MPAL) system was developed for the purpose of addressing the identified weaknesses. Two classes of twenty-six third grade students participated in the present research to examine the unique contribution of MPAL to collaborative EFL reading activities. The collaborative behavior of elementary EFL learners was videotaped and analyzed. Detailed analysis of the videotaped behavior indicated that MPAL helped improve collaboration in elementary school level EFL learners and promotes their reading motivation.